New Atheist’s View on Theological: A Critical Analysis on Sam Harris’ Thought - Sholihin, Zahrul Fata; Fatah Yasin, Roudlotul Firdaus; Annada, Fasya Tharra (FIKRAH, 2025)
The New Atheism is emerging and becoming a global phenomenon, especially after 9/11, which was popularized by four well-known authors called the Four Horsemen. One of the new atheist figures, Sam Harris, wrote a book titled ‘The End of Faith Religion: Terror, and the Future of the Reason’ that contains critiques on religions, mainly Islam. Harris argues that Islam is dangerous because its Holy Book, the Qur’an, is thought to support jihad, which ultimately leads to acts of terrorism. Based on that, this study aims to critically analyze Sam Harris’s interpretation of theological sources of authority, specifically the Qur’an. This study using a qualitative research method and a hermeneutical approach. These data collection and analysis techniques allow more nuanced discussions on New Atheism as interpreted by Harris. This study argues that understanding religion requires philosophical, theological, and historical interpretation rather than solely a scientific or empirical lens. The findings of this study that Harris’ explanation about the Qur’an is superficial and misleading, primarily due to his limited understanding of Islam and the Qur’an itself. This study contributes to the development of Islamic science which can be studied in a multidisciplinary manner without ignoring the holy book as the main source